2002
DOI: 10.1140/epje/i2002-10010-8
|View full text |Cite
|
Sign up to set email alerts
|

Peeling model for cell detachment

Abstract: In many experimental situations, the adhesion of cells to solid substrates is due to non-covalent chemical bonds. It is the thesis of this paper that many phenomena occurring in cell detachment experiments, such as in I (E. Decavé, G. Garriver, Y. Brechet, B. Fourcade, F. Bruckert, Biophys. J. 82, 2383 (2002)), result from the static and dynamic properties of the adhesive bridges at the extreme margin of the cell. This region defines the adhesive belt where the distribution of connected bonds crosses over to z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 4 publications
2
30
0
Order By: Relevance
“…Below the threshold, the front velocity vf adjusts to the peeling velocity vr and, above the threshold, the peeling velocity has to overcome a limited front velocity. This slightly modifies the expression of the detachment rate, a posteriori justifying the use of this peeling model to describe living cell detachment (Garrivier et al, 2002). Detachment of living motile cells is nevertheless intrinsically different from that of passive objects, in the sense that it is not due to the rupture of a static equilibrium but to the unbalance between two dynamic phenomena.…”
Section: Mechanosensitivity Of D Discoideum Cellsmentioning
confidence: 96%
See 2 more Smart Citations
“…Below the threshold, the front velocity vf adjusts to the peeling velocity vr and, above the threshold, the peeling velocity has to overcome a limited front velocity. This slightly modifies the expression of the detachment rate, a posteriori justifying the use of this peeling model to describe living cell detachment (Garrivier et al, 2002). Detachment of living motile cells is nevertheless intrinsically different from that of passive objects, in the sense that it is not due to the rupture of a static equilibrium but to the unbalance between two dynamic phenomena.…”
Section: Mechanosensitivity Of D Discoideum Cellsmentioning
confidence: 96%
“…More precisely, we observed that, for CIPCtreated cells, detachment corresponds to a transition between immobility of the cell-substrate contact area and irreversible peeling. The limit force and the relationship between the peeling velocity and the force are described by a passive model of the cell edge under tension that has been described elsewhere (Decave et al, 2002a;Garrivier et al, 2002). The speed of the front edge velocity during the fast cell-substrate area bursts (vp=0.40 µm second -1 ) obviously sets a limit to cell attachment under flow.…”
Section: Mechanosensitivity Of D Discoideum Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peeling is an important and ubiquitous process in biology and engineering [1][2][3][4][5][6]. For a nominally inextensible film, the peel strength is controlled by the peel angle and the adhesion energy of the film attached to the substrate [7].…”
Section: Introductionmentioning
confidence: 99%
“…Steven-Fountain et al [20] used a similar approach to explain the effect of a flexible substrate on pressure-sensitive adhesive performance. Garrivier et al [21] presented a peeling model for cell detachment from cytoplasmic membranes, using the analogy of adhesion and fracture. Ciccotti et al [22] modeled the complex dynamics of peeling adhesive tape as two-dimensional fracture propagation.…”
Section: Introductionmentioning
confidence: 99%